Conservation and Safeguarding Cultural Identity of a Local Community at Tjong A Fie Mansion in Medan - Efin Shu (Universitas Pelita Harapan Medan Campus, 2022)
Tjong A Fie Mansion is the only Chinese museum which is located at the heart of Medan City. It is the only ancient building which stands still with its vintage style in the commercial street surrounded by shops and restaurants. Despite of the modernization happening surrounding Tjong A Fie mansion, it does not grind the authenticity and cultural identity of the mansion. The mansion is kept as it is without being transformed into a business area. Therefore, the purpose of this research is to find out the conservation and safeguarding cultural identity of a local community effort at Tjong A Fie Mansion. This research is using qualitative method as its research approach. As the data collection method, the writer uses in-depth interview with informants, email interview, and observation. The data is validated using source triangulation.The results of the research show that some conservation efforts have been done at Tjong A Fie Mansion and the heritage use intensity is low. Some efforts still need to be done to protect cultural traditions. Most parts of the mansion are still authentic and some efforts need to be done to preserve the genuine experience of the mansion. Some efforts to conserve and safeguard the cultural identity which are related to education have also been done.